HDL flux is higher in patients with nonalcoholic fatty liver disease - McCullough, Arthur (Am J Physiol Endocrinol Metab, 2019)
Altered lipid metabolism and inflammation are involved in the pathogenesis of both nonalcoholic fatty liver disease (NAFLD) and cardiovascular disease (CVD). Even though high-density lipoprotein (HDL), a CVD protective marker, is decreased, whether HDL metabolism and function are perturbed in NAFLD are currently unknown. We examined the effect of NAFLD and disease severity on HDL metabolism and function in patients with biopsy-proven simple steatosis (SS), nonalcoholic steatohepatitis (NASH), and healthy controls. HDL turnover and HDL protein dynamics in SS (n = 7), NASH (n = 8), and healthy controls (n = 9) were studied in vivo. HDL maturation and remodeling, antioxidant, cholesterol efflux properties, and activities of lecithin-cholesterol ester acyltransferase and cholesterol ester transfer protein (CETP) were quantified using in vitro assays. All patients with NAFLD had increased turnover of both HDL cholesterol (HDLc; 0.16 ± 0.09 vs. 0.34 ± 0.18 days, P < 0.05) and apolipoprotein A1 (ApoAI) (0.26 ± 0.04 vs. 0.34 ± 0.06 days, P < 0.005) compared with healthy controls. The fractional catabolic rates of other HDL proteins, including ApoAII (and ApoAIV) were higher (P < 0.05) in patients with NAFLD who also had higher CETP activity, ApoAI/HDLc ratio (P < 0.05). NAFLD-induced alterations were associated with lower antioxidant (114.2 ± 46.6 vs. 220.5 ± 48.2 nmol·mL(−1)·min(−1)) but higher total efflux properties of HDL (23.4 ± 1.3% vs. 25.5 ± 2.3%) (both P < 0.05), which was more pronounced in individuals with NASH. However, no differences were observed in either HDL turnover, antioxidant, and cholesterol efflux functions of HDL or HDL proteins’ turnover between subjects with SS and subjects with NASH. Thus, HDL metabolism and function are altered in NAFLD without any significant differences between SS and NASH.